PROPOSED METHODOLOGY OF A GEOGRAPHIC INFORMATION SYSTEM OPEN SOURCE. REGIONAL DIRECTION OF CARTAGO. MINISTRY OF PUBLIC EDUCATION - Solano-Mayorga, Manuel Antonio; Rodríguez-Soto, Francisco (Revista Geográfica de América Central., 2015)
This article aims to demonstrate a prototype tool developed with the support of a Geographic Information System (GIS) of free nature, which can be applied in the handling of information of the Regional Directorate, Cartago, the Ministry of Public Education Costa Rica. Similarly, there is a need for further dissemination of the free options that can be used more frequently in solving the various problems that are directly related to the management of spatial information. The need to implement free solutions must become a great option to give a chance to national institutions to use spatial analysis tools for free. The reasons are varied, social, economic, technological, among others, which should work to become a solution within reach of a vast majority of institutions. All this will help to generate new knowledge and which will support various decision making processes. In this paper the application of gvSig as a viable, economic and technological alternative is proposed for the Ministry of Education to monitor part of the institutional infrastructure, and based on this to better planning in the various processes involved as a special component the geographical space.